An Investigation of Students Autonomous Learning Performance during Covid-19 Outbreak: A Case Study - Made Wahyu Mahendra (Universitas Muhammadiyah Jember, 2021)
Covid-19 outbreak has brought a great disruption to instructional process. Needless to say, the goal of instructional process needs to shift from student centred learning to promoting learner autonomy. Yet, it is important to conduct a study which learn the students’ capacity to be autonomous. This present study aims at investigating learners’ autonomous learning capacity during this outbreak. The researcher employed a mix method design where the data obtained were presented in both quantitative and qualitative perspectives. There are total 30 higher education students chosen to be the subjects of the present study. The data were gathered through different instruments; questionnaire and semi structured interview. The questionnaire comprises five major aspects in measuring learners’ capacity in autonomous learning. In order to achieve the credibility of the data, the researchers’ employs triangulation of data. The results of the study showed that learners have the capacity of autonomous learning to some extent. Learners are quite self-directed in the aspects of defining content and progression, monitor the procedure of acquiring knowledge, and doing self-evaluation. Meanwhile, the aspects of setting objectives and selecting method to learn need to be improved. The findings imply that optimization of learning is a must despite all boundaries that challenge both learners and educators.